High-nonlinearity perovskite nanocrystal doped chalcogenide glass and preparation method thereof

By introducing CsPbBr3 perovskite nanocrystals into Ge2S3 sulfur-based glass and performing microcrystalline heat treatment, a highly nonlinear perovskite nanocrystal doped sulfur-based glass was prepared, which solved the problem of insufficient photothermal stability under high optical power excitation by perovskite materials, and achieved efficient nonlinear optical performance and optical limiting performance.

CN119841553APending Publication Date: 2025-04-18NINGBO UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510069046.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing perovskite materials have problems with insufficient photothermal stability under high optical power excitation, especially when used in nonlinear photonic devices, it is difficult to meet the requirements of high efficiency and stability.

Method used

By introducing CsPbBr3 perovskite nanocrystals into Ge2S3 sulfur-based glass, microcrystalline heat treatment technology was used to prepare highly nonlinear perovskite nanocrystal doped sulfur-based glass. The glass exhibits significant improvements in high photothermal stability, nonlinear absorption coefficient and nonlinear refractive index in the wavelength range of 800 to 920 nm.

Benefits of technology

High nonlinear optical performance in the wavelength range of 800-920nm is achieved, with infrared light transmittance up to 60-80%, the maximum value of nonlinear absorption coefficient β is 27.1cm/GW, the maximum value of nonlinear refractive index n2 is 8.60×10-17m2/W, and the minimum optical limiting threshold can reach 32.4μJ/cm2, which is suitable for the manufacturing of high-performance optical limiting devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841553A_ABST
    Figure CN119841553A_ABST
Patent Text Reader

Abstract

The high-nonlinearity perovskite nanocrystal doped chalcogenide glass disclosed by the invention is CsPbBr3 perovskite nanocrystal doped Ge2S3 chalcogenide glass, the molar composition formula is 99 (40Ge-60S)-1 (CsBr-PbBr2), the high-nonlinearity perovskite nanocrystal doped chalcogenide glass contains CsPbBr3 perovskite nanocrystals with the grain size of 10-100nm, the high-nonlinearity perovskite nanocrystal doped chalcogenide glass is obtained by carrying out micro-crystallization heat treatment on a Ge2S3 chalcogenide glass material doped with CsPbBr3 perovskite, the temperature of the micro-crystallization heat treatment is 320-330 DEG C, and the time of the micro-crystallization heat treatment is 3-10 hours. Within the wavelength range of 800-920 nm, the chalcogenide glass has the advantages of high photo-thermal stability, high transmittance, high hardness, high nonlinear absorption coefficient, high nonlinear refractive index and the like, the infrared light transmittance of the chalcogenide glass can reach 60-80%, the maximum value of the nonlinear absorption coefficient beta is 27.1 cm / GW, the maximum value of the nonlinear refractive index n2 is 8.60 * 10 <-17 > m < 2 > / W, and the minimum optical limiting threshold value can reach 32.4 mu J / cm < 2 >. The method is expected to show huge application value in optical limiting application based on laser protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanocrystal-doped chalcogenide glass, and in particular to a highly nonlinear perovskite nanocrystal-doped chalcogenide glass and a preparation method thereof. Background Art

[0002] In addition to excellent optoelectronic properties, perovskites also have excellent nonlinear optical properties such as high multiphoton cross-section, large nonlinear refractive index, and broadband modulation characteristics. They are emerging nonlinear optical materials with great potential in nonlinear photonic applications such as multiphoton imaging, upconversion lasers, and optical limiting. However, the low photothermal stability of perovskites is still the main reason that hinders their application in optical devices, especially nonlinear photonic devices that require high optical power excitation. Among the two major types of perovskite systems (all-inorganic and organic-inorganic hybrid), all-inorganic perovskites have higher photothermal stability than organic-inorganic hybrid perovskites, so they are more likely to be used in nonlinear photonic devices first. However, since all-inorganic perovskites composed of halogen ion bonds are easily deliquesced by oxygen and water vapor in the air, they must be encapsulated in practical applications.

[0003] Existing research results show that optical glass with high optical transparency and high optical stability is an excellent material for encapsulating all-inorganic perovskites. The all-inorganic perovskite encapsulated by glass not only solves the problems of deliquescence and photothermal stability, but also maintains the original luminescence properties of the perovskite. More importantly, the overall nonlinear optical properties of the glass are also improved after the composite all-inorganic perovskite. Sulfur-based glass has the highest nonlinear optical performance among the currently known optical glasses and excellent compatibility with inorganic perovskites. Ge-S binary sulfide glass is an environmentally friendly sulfide glass system that does not contain toxic and heavy metal elements. Their network structure is mainly composed of stable [GeS4] tetrahedrons, so it has high photothermal stability. In addition, in terms of nonlinear optical functions, the Ge-S system has better performance than other sulfide glasses. Therefore, it is a solution worth exploring to improve the nonlinear performance of glass by embedding perovskite nanocrystals into the Ge-S chalcogenide glass matrix. Therefore, the inventors studied the introduction of CsPbBr3 perovskite nanocrystals into Ge2S3 chalcogenide glass and proposed a highly nonlinear perovskite nanocrystal-doped chalcogenide glass and a preparation method thereof. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a highly nonlinear perovskite nanocrystal-doped chalcogenide glass and a preparation method thereof in view of the deficiencies of the prior art. In the wavelength range of 800 to 920 nm, the perovskite nanocrystal-doped chalcogenide glass of the present invention has the advantages of high photothermal stability, high transmittance, high hardness, high nonlinear absorption coefficient, high nonlinear refractive index, etc. Its infrared light transmittance can reach 60 to 80%, the maximum value of the nonlinear absorption coefficient β is 27.1 cm / GW, and the maximum value of the nonlinear refractive index n2 is 8.60×10 -17 m 2 / W, the light limiting threshold can be as low as 32.4μJ / cm 2 , which is expected to show great application value in optical limiting applications based on laser protection.

[0005] The technical solution adopted by the present invention to solve the above technical problems is: highly nonlinear perovskite nanocrystal-doped chalcogenide glass, the perovskite nanocrystal-doped chalcogenide glass is CsPbBr3 perovskite nanocrystal-doped Ge2S3 chalcogenide glass, the molar composition formula of the perovskite nanocrystal-doped chalcogenide glass is 99(40Ge-60S)-1(CsBr-PbBr2), the perovskite nanocrystal-doped chalcogenide glass contains CsPbBr3 perovskite nanocrystals with a grain size of 10 to 100 nm, the perovskite nanocrystal-doped chalcogenide glass is obtained by microcrystalization heat treatment of Ge2S3 chalcogenide glass material doped with CsPbBr3 perovskite, the temperature of the microcrystalization heat treatment is 320 to 330°C, and the time is 3 to 10 hours.

[0006] In a preferred embodiment, the temperature of the microcrystallization heat treatment is 320°C or 330°C. The maximum value of the nonlinear absorption coefficient β of the perovskite nanocrystal-doped chalcogenide glass obtained by microcrystallization heat treatment is 27.1 cm / GW. The CsPbBr3 perovskite nanocrystals contained therein are about 23 nm, which is 2.3 times the nonlinear absorption coefficient of the Ge2S3 matrix glass. The maximum value of the nonlinear refractive index n2 of the perovskite nanocrystal-doped chalcogenide glass is 8.60×10 -17 m 2 / W, which is 2.3 times the nonlinear refractive index of Ge2S3 matrix glass. This shows that the perovskite nanocrystal-doped chalcogenide glass obtained by microcrystallization heat treatment has excellent nonlinear optical properties, and its minimum optical limiting threshold is 32.4μJ / cm 2 , which is suitable for use in the field of optical limiting device manufacturing.

[0007] The method for preparing the highly nonlinear perovskite nanocrystal-doped chalcogenide glass comprises the following steps:

[0008] S1. Raw material preparation and vacuum packaging:

[0009] According to the molar composition of the perovskite nanocrystal-doped chalcogenide glass, the required mass of each raw material is first calculated, and the high-purity germanium, sulfur, cesium bromide, and lead bromide raw materials are weighed using an electronic balance, and the weighing error is controlled within ±0.001g. Then, all the raw materials are placed in a dry and clean quartz tube, and the quartz tube is evacuated to 10 -5 Pa or less, the raw materials are encapsulated in a quartz tube;

[0010] S2. Raw material melting and mixing:

[0011] The packaged quartz tube is placed in a rocking furnace for high-temperature melting at 950°C for 12 hours. After the melting is completed, the quartz tube is taken out of the rocking furnace and then quickly immersed in water at room temperature to quench the packaged melt. After the wall is observed to be detached, it is immediately taken out to obtain a semi-finished Ge2S3 chalcogenide glass with CsPbBr3 perovskite components added in the quartz tube.

[0012] S3, annealing to relieve stress:

[0013] The semi-finished Ge2S3 chalcogenide glass with CsPbBr3 perovskite component added is annealed together with the quartz tube, the annealing temperature is 310-320°C, the annealing time is 10-14h, and after the annealing is completed, the temperature is cooled to room temperature at a cooling rate of 9-10°C / h, and then the quartz tube is taken out of the annealing furnace, and the quartz tube is opened to obtain the finished Ge2S3 chalcogenide glass doped with CsPbBr3 perovskite;

[0014] S4, microcrystallization heat treatment:

[0015] The finished Ge2S3 chalcogenide glass doped with CsPbBr3 perovskite is subjected to microcrystallization heat treatment at 320-330°C for 3-10 hours to obtain the perovskite nanocrystal-doped chalcogenide glass, whose molar composition formula is 99(40Ge-60S)-1(CsBr-PbBr2).

[0016] Preferably, in step S4, the temperature of the microcrystallization heat treatment is 320°C or 330°C.

[0017] Compared with the prior art, the present invention has the following advantages:

[0018] (1) The inventors have successfully synthesized CsPbBr3 perovskite nanocrystals in a chalcogenide glass composed of Ge2S3, and obtained CsPbBr3 perovskite nanocrystal-doped Ge2S3 chalcogenide glass with high transmittance, high nonlinear absorption coefficient and high nonlinear refractive index. After testing, the perovskite nanocrystal-doped chalcogenide glass of the present invention has a very high nonlinear absorption coefficient and nonlinear refractive index in the wavelength range of 800 to 920 nm. The maximum value of its nonlinear absorption coefficient β is 27.1 cm / GW, and the maximum value of its nonlinear refractive index n2 is 8.60×10 -17 m 2 / W, and the infrared light transmittance can reach 60-80%, and the Vickers hardness can reach up to 270kg / mm 2 , with high photothermal stability, it is an excellent nonlinear optical material for preparing nonlinear photonic devices;

[0019] (2) The inventors encapsulated the all-inorganic metal halide perovskite CsPbBr3 into Ge2S3 chalcogenide glass. The obtained CsPbBr3 perovskite nanocrystal-doped Ge2S3 chalcogenide glass not only fundamentally solved the problems of perovskite's easy deliquesce and photothermal stability, but also improved the overall nonlinear optical properties of Ge2S3 chalcogenide glass after doping with CsPbBr3 perovskite nanocrystals.

[0020] (3) The optical limiting threshold of the perovskite nanocrystal-doped chalcogenide glass of the present invention can reach as low as 32.4 μJ / cm 2 , it has high optical limiting performance and is a new type of broadband laser protection material with excellent performance. It can be used as an excellent material for preparing high-performance optical limiting devices and is expected to show great application value in optical limiting applications based on laser protection;

[0021] (4) The present invention adopts a vacuum melting method to prepare chalcogenide glass, which can ensure that the semi-finished Ge2S3 chalcogenide glass is not affected by oxidation and evaporation, and ensure the stability of the chemical components of CsPbBr3 perovskite, thereby preparing highly nonlinear perovskite nanocrystal-doped chalcogenide glass with high photothermal stability;

[0022] (5) The crystallinity of the CsPbBr3 perovskite nanocrystals contained in the highly nonlinear perovskite nanocrystal-doped chalcogenide glass of the present invention can be flexibly adjusted according to the temperature and time of the microcrystallization heat treatment, thereby enabling the regulation of the corresponding performance parameters. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the experimental setup used for the Z-scan experiment;

[0024] Figure 2The nonlinear absorption result curves of the Z scanning experiments of the glass samples of the blank group, comparative example 1, and examples 1 to 5 at the same light wavelength (800nm) are shown in FIG. Figure 2 The middle numbers ① to ⑦ correspond to the blank group, comparative example 1, and examples 1 to 5, respectively;

[0025] Figure 3 The nonlinear refraction result curves of the closed-cell Z-scan experiment of the glass samples of the blank group, comparative example 1, and examples 1 to 5 at the same light wavelength (800 nm) are shown in FIG. Figure 3 The middle numbers ① to ⑦ correspond to the blank group, comparative example 1, and examples 1 to 5, respectively;

[0026] Figure 4 The transmission spectra of the glass samples of the blank group, comparative example 1, and examples 1 to 5 in different light bands (0.5 to 12 μm);

[0027] Figure 5 XRD patterns of the glass samples of the blank group, comparative example 1, and examples 1 to 5;

[0028] Figure 6 It is the grain size spectrum of the glass samples of comparative example 1 and examples 1 to 5;

[0029] Figure 7 These are the optical limiting spectra of the glass samples of Example 2, Example 3, and Example 5. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below with reference to the accompanying drawings.

[0031] The molar composition formula of the highly nonlinear perovskite nanocrystal doped chalcogenide glass of Examples 1 to 5 is 99(40Ge-60S)-1(CsBr-PbBr2), and the perovskite nanocrystal doped chalcogenide glass contains CsPbBr3 perovskite nanocrystals with a grain size of 10 to 100 nm. The perovskite nanocrystal doped chalcogenide glass is obtained by microcrystalization heat treatment of Ge2S3 chalcogenide glass material doped with CsPbBr3 perovskite, and the temperature of the microcrystalization heat treatment is 320 to 330°C, and the time is 3 to 10 hours.

[0032] The method for preparing the highly nonlinear perovskite nanocrystal-doped chalcogenide glass of Examples 1 to 5 comprises the following steps:

[0033] S1. Raw material preparation and vacuum packaging:

[0034] According to the molar composition of perovskite nanocrystal-doped chalcogenide glass, the required mass of each raw material was calculated first, and the high-purity germanium (99.999%, 5N), sulfur (5N), cesium bromide (4N), and lead bromide (4N) raw materials were weighed using an electronic balance, and the weighing error was controlled within ±0.001g. Then all the raw materials were placed in a dry and clean quartz tube, and the quartz tube was evacuated to 10 -5 Pa or less, the raw materials are encapsulated in a quartz tube;

[0035] S2. Raw material melting and mixing:

[0036] The packaged quartz tube is placed in a rocking furnace for high-temperature melting at 950°C for 12 hours. After the melting is completed, the quartz tube is taken out of the rocking furnace and then quickly immersed in water at room temperature to quench the packaged melt. After the wall is observed to be detached, it is immediately taken out to obtain a semi-finished Ge2S3 chalcogenide glass with CsPbBr3 perovskite components added in the quartz tube.

[0037] S3, annealing to relieve stress:

[0038] The semi-finished Ge2S3 chalcogenide glass to which the CsPbBr3 perovskite component is added is annealed together with the quartz tube, the annealing temperature is 310-320°C (about 30°C lower than the glass transition temperature), and the annealing time is 10-14h to eliminate the internal stress of the glass material. After the annealing is completed, the temperature is lowered to room temperature at a cooling rate of 9-10°C / h, and then the quartz tube is taken out of the annealing furnace and opened to obtain the finished Ge2S3 chalcogenide glass doped with CsPbBr3 perovskite;

[0039] S4, microcrystallization heat treatment:

[0040] The finished Ge2S3 chalcogenide glass doped with CsPbBr3 perovskite is subjected to microcrystallization heat treatment at 320-330°C for 3-10 hours to obtain perovskite nanocrystal-doped chalcogenide glass, whose molar composition formula is 99(40Ge-60S)-1(CsBr-PbBr2).

[0041] The preparation methods of highly nonlinear perovskite nanocrystal-doped chalcogenide glasses of Examples 1 to 5 differ only in the temperature and time of microcrystallization heat treatment, and the other steps and parameters are the same. Specifically, the temperature and time of microcrystallization heat treatment in Examples 1 to 5 are 320°C and 3h, 320°C and 5h, 320°C and 10h, 330°C and 3h, and 330°C and 5h, respectively.

[0042] For comparison, the glass of the blank group and comparative example 1 were selected. The difference from the embodiment is that the glass of the blank group is Ge2S3 matrix glass without adding CsPbBr3 perovskite; the heat treatment time of the glass of comparative example 1 is 0h, that is, no microcrystallization heat treatment is performed.

[0043] For simplicity, Figure 2 , Figure 3 , Figure 4 , Figure 5 In the table, Base or base ChG, GSC320℃-0h, GSC320℃-3h, GSC320℃-5h, GSC320℃-10h, GSC330℃-3h, and GSC330℃-5h represent the glass samples of the blank group, comparative example 1, example 1, example 2, example 3, example 4, and example 5, respectively.

[0044] Table 1 lists the mechanical and optical performance parameters of the glass samples of the blank group, comparative example 1, and examples 1 to 5, among which H v Represents Vickers hardness, E opg It can be seen from Table 1 that the hardness value of comparative example 1 is higher than that of the blank group, which indicates that the addition of perovskite can effectively enhance the mechanical properties of the glass, and the hardness values ​​of Examples 1 to 5 are all higher than those of comparative example 1, which indicates that the perovskite nanocrystals precipitated in the matrix glass by microcrystallization heat treatment can improve the overall structure of the glass micro-network, thereby enhancing its mechanical strength.

[0045] Table 1: Mechanical and optical properties of glass samples

[0046]

[0047] For all glass samples, we used open-hole and closed-hole Z-scan experiments to measure their nonlinear absorption coefficients and nonlinear refractive indices. The five wavelengths selected were 800nm, 830nm, 860nm, 890nm and 920nm. The schematic diagram of the experimental setup is shown in Figure 2. Figure 1As shown. The laser light source is a titanium sapphire femtosecond laser (Chameleon Ultra II, USA), and its excitation light source is adjustable, with an adjustment range of 680-1080nm, a repetition frequency of 80MHz, a pulse width of 140fs, and a power stability of ±3%. The laser first passes through a high-reflection mirror and is divided into two beams by a semi-transparent and semi-reflective beam splitter (reflectivity and transmittance are 45% and 55% respectively). One beam of light is detected by power detector 1 as a reference light source of incident power, and the other beam of light is focused by a double convex mirror and irradiated onto the glass sample. The transmitted beam is received by optical power detector 2. The power signals received by power detector 1 and power detector 2 are respectively input into the EM2000 dual-channel power meter of Coherent. During the experiment, the position of the sample is adjusted by a stepper motor controller, and the readings of the power meter are recorded to obtain a set of Z-scan data corresponding to the sample position and the transmitted power. The above tests are all carried out at room temperature.

[0048] The open hole Z scanning test result curves of the glass samples of the blank group, comparative example 1, and examples 1 to 5 at the same light wavelength (800nm) are shown in FIG. Figure 2 .from Figure 2 It can be seen that the normalized transmittance at the focus of the samples (Examples 1 to 5) that have undergone microcrystallization heat treatment shows a significant decreasing trend compared to the blank group, indicating that the nonlinear absorption of the glass will gradually increase with the introduction and growth of perovskite crystals.

[0049] Figure 3 It is the nonlinear refraction result curve of the closed-cell Z-scan experiment of the glass samples of the blank group, comparative example 1, and examples 1 to 5 at the same light wavelength (800nm). Figure 3 The results show that the difference between the peak and valley values ​​of the transmittance of the glass samples of Examples 1 to 5 also shows a significant increasing trend compared with the glass samples of the blank group, which indirectly reflects that the glass samples of Examples 1 to 5 have a larger nonlinear refractive index.

[0050] Table 2 lists the nonlinear absorption coefficient β and nonlinear refractive index n2 of each glass sample at different wavelengths. The nonlinear absorption coefficient β and nonlinear refractive index n2 of the blank group of glass samples at 920nm wavelength are 3.1cm / GW and 0.89×10 -17 m 2 / W, is the minimum value, and Example 3 at a wavelength of 800nm ​​has the largest nonlinear absorption coefficient β and nonlinear refractive index n2, which are 27.1cm / GW and 8.60×10 -17 m 2 / W.

[0051] Table 3 lists the optical limiting thresholds OLT of some glass samples at different wavelengths. The optical limiting threshold of the glass sample of Example 2 at a wavelength of 950 nm is 192.1 μJ / cm 2 , is the maximum value. Example 3 at a wavelength of 800 nm has the smallest optical limiting threshold OTL, which is 32.4 μJ / cm 2 It is worth pointing out that we characterized the optical limiting properties of the three glass samples with the highest nonlinear absorption coefficients, because stronger nonlinear absorption indicates that they will have stronger optical limiting performance.

[0052] As for the glass sample of embodiment 3, due to the perovskite crystal embedded in Ge2S3 matrix glass, the size of the grain and the change of the local environment of the glass, its gap state may become more obvious, which may be caused by the interaction between atoms or surface defects. The local gap state can be expressed as a specific energy level, making the nonlinear absorption process more efficient. So at a specific wavelength, the β value will increase with the increase of the heat treatment temperature and time, improving nonlinear absorption. From the data in Table 2, it can be seen that due to the photon energy of 800nm ​​wavelength and the defect state in the nanocrystalline glass sample have a better resonance effect at the focus, enhancing nonlinear absorption and nonlinear refraction, therefore compared with other wavelengths, under the radiation of 800nm ​​laser wavelength, with the increase of microcrystallization heat treatment temperature and time, the nonlinear absorption coefficient β and nonlinear refractive index n2 of the glass sample are significantly increased, showing stronger nonlinear absorption and refraction effect. Simultaneously, from the overall analysis, due to the quantum effect of perovskite nanocrystals, the perovskite nanoparticles that are confined in the matrix glass cause the valence band and the conduction band to decompose into a series of discrete energy levels, so that the nonlinear characteristic increases with the increase of crystallinity at the incident wavelength. Through the change and interaction of electron quantum states in the light field, the intraband transitions of electrons in the matrix glass increase, resulting in changes in nonlinear absorption. Based on the changes in nonlinear absorption, we can measure the optical limiting threshold of the glass sample to evaluate the strength of its optical limiting ability. Finally, we obtained CsPbBr3 perovskite nanocrystals embedded in Ge2S3 chalcogenide glass with the smallest optical limiting threshold.

[0053] Table 2: Nonlinear absorption coefficient β and nonlinear refractive index n2 of each glass sample at different wavelengths

[0054]

[0055] Table 3: Optical limiting thresholds (OTL) of some glass samples at different wavelengths

[0056]

[0057] Figure 4The transmittance spectra of the glass samples of the blank group, comparative example 1 and examples 1 to 5 in the visible light band (0.5 to 12 μm) are shown. Figure 4 It can be seen that in the wide range from near-infrared to mid-infrared, each glass sample has a high infrared light transmittance.

[0058] Figure 5 The XRD patterns of the glass samples of the blank group, comparative example 1, and examples 1 to 5 are shown. Figure 5 It can be seen that after different microcrystallization heat treatment temperatures (320-330°C) and times (3-10h), obvious crystal diffraction peaks appeared in the spectrum, which are consistent with the diffraction peak positions of standard CsPbBr3 crystals (PDF No.54-752), indicating that perovskite nanocrystals have been precipitated in the glass samples of Examples 1 to 5. Figure 6 The grain size spectra of the glass samples of Comparative Example 1 and Examples 1 to 5 are shown, and the variation trend of the perovskite crystal size in the glass matrix can be seen. Figure 5-6 It can be seen that the changes in the crystallinity of the crystals inside the glass can be summarized as follows according to different temperatures and times:

[0059] (1) For the blank group, simply Figure 5 From the XRD spectrum, it can be seen that the interior of the glass is uniform and no crystals appear;

[0060] (2) For Comparative Example 1, according to Figure 5 From the XRD spectrum, we can see that there are tiny crystal diffraction peaks. At this time, the crystals are still in the nucleus state and the aggregation degree is small, so the diffraction peaks are not obvious.

[0061] (3) For Examples 1 to 5, according to Figure 5 It can be seen from the XRD spectrum that with the introduction of the microcrystallization heat treatment process, the intensity of these diffraction peaks has increased significantly and become sharper, indicating that the size and number of perovskite crystals in the glass have a tendency to increase and increase. According to the Ostwald ripening theory, the nanocrystals inside the glass further aggregate and the crystal size further increases. With the extension of the microcrystallization heat treatment time or the increase of the temperature, the diffraction peak intensity of the perovskite crystal has not shown an obvious trend of continued enhancement, which indicates that the crystallinity of the perovskite crystal will quickly saturate with the introduction of the microcrystallization heat treatment process. Combined with Figure 6 After analyzing the grain size diagram, the existence of crystallinity saturation phenomenon of CsPbBr3 nanocrystals can be confirmed.

[0062] Figure 7The light limiting spectra of the glass samples of Example 2, Example 3, and Example 5 show that the normalized transmittance of each sample decreases with the increase of the incident light energy density, indicating that they all have light limiting characteristics. By performing specific light limiting threshold value tests on them, it is found that the lowest light limiting threshold can reach 32.4 μJ / cm 2 The light energy density when the logarithmic normalized transmittance drops to -3dB (i.e. the linear normalized transmittance drops to 0.707 times of the original value) is defined as the optical limiting threshold OLT of the material.

Claims

1. Highly nonlinear perovskite nanocrystal-doped chalcogenide glass, characterized in that: The perovskite nanocrystal-doped chalcogenide glass is CsPbBr3 perovskite nanocrystal-doped Ge2S3 chalcogenide glass. The molar composition formula of the perovskite nanocrystal-doped chalcogenide glass is 99(40Ge-60S)-1(CsBr-PbBr2). The perovskite nanocrystal-doped chalcogenide glass contains CsPbBr3 perovskite nanocrystals with a grain size of 10 to 100 nm. The perovskite nanocrystal-doped chalcogenide glass is obtained by subjecting Ge2S3 chalcogenide glass material doped with CsPbBr3 perovskite to microcrystalization heat treatment. The temperature of the microcrystalization heat treatment is 320 to 330° C. and the time is 3 to 10 hours.

2. The highly nonlinear perovskite nanocrystal-doped chalcogenide glass according to claim 1, characterized in that: The temperature of the microcrystallization heat treatment is 320°C or 330°C.

3. The highly nonlinear perovskite nanocrystal-doped chalcogenide glass according to claim 1, characterized in that: The maximum nonlinear absorption coefficient β of the perovskite nanocrystal-doped chalcogenide glass is 27.1 cm / GW, and the maximum nonlinear refractive index n2 is 8.60×10 -17 m 2 / W.

4. The method for preparing the highly nonlinear perovskite nanocrystal-doped chalcogenide glass according to claim 1, characterized in that: The following steps are involved: S1. Raw material preparation and vacuum packaging: According to the molar composition of the perovskite nanocrystal-doped chalcogenide glass, the required mass of each raw material is first calculated, and the high-purity germanium, sulfur, cesium bromide, and lead bromide raw materials are weighed using an electronic balance, and the weighing error is controlled within ±0.001g. Then, all the raw materials are placed in a dry and clean quartz tube, and the quartz tube is evacuated to 10 -5 Pa or less, the raw materials are encapsulated in a quartz tube; S2. Raw material melting and mixing: The packaged quartz tube is placed in a rocking furnace for high-temperature melting at 950°C for 12 hours. After the melting is completed, the quartz tube is taken out of the rocking furnace and then quickly immersed in water at room temperature to quench the packaged melt. After the wall is observed to be detached, it is immediately taken out to obtain a semi-finished Ge2S3 chalcogenide glass with CsPbBr3 perovskite components added in the quartz tube. S3, annealing to relieve stress: The semi-finished Ge2S3 chalcogenide glass with CsPbBr3 perovskite component added is annealed together with the quartz tube, the annealing temperature is 310-320°C, the annealing time is 10-14h, and after the annealing is completed, the temperature is cooled to room temperature at a cooling rate of 9-10°C / h, and then the quartz tube is taken out of the annealing furnace, and the quartz tube is opened to obtain the finished Ge2S3 chalcogenide glass doped with CsPbBr3 perovskite; S4, microcrystallization heat treatment: The finished Ge2S3 chalcogenide glass doped with CsPbBr3 perovskite is subjected to microcrystallization heat treatment at 320-330°C for 3-10 hours to obtain the perovskite nanocrystal-doped chalcogenide glass, whose molar composition formula is 99(40Ge-60S)-1(CsBr-PbBr2).

5. The method for preparing highly nonlinear perovskite nanocrystal-doped chalcogenide glass according to claim 4, characterized in that: In step S4, the temperature of the microcrystallization heat treatment is 320°C or 330°C.

Citation Information

Cited By

  • CsSnCl3 nanocrystalline doped chalcogenide glass and acousto-optic application thereof

    CN121361957A